The The Life Of The Ae Ba’i Community, Urban Village Of Kota Ratu , Ende Utara Distric, Ende Regency (Overview Of Socio Economic And Educational Conditions) - Anita; Hasti Sulaiman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
The purpose of this study is to determine the life of the Ae Ba'i urban village of Kota Ratu, Ende Utara District, Ende Regency in terms of socio-economic conditions and education level. The research method used is qualitative research. Data collection techniques consist of interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that the life of the Aebai'i people was seen from the socio-economic conditions which were still very low. This can be seen from the livelihoods of the people who are not permanent, there are garden farmers, fishermen, weaving, and to make ends meet, they have to look for firewood, and dry shells / coconut shells to sell. Some 13 year olds have had to leave the village to migrate to Arabia and Malaysia to help their parents fulfill their daily needs. The level of education of the Ae Ba'i community is still very low, this is evident in school-age children who do not go to school and prefer to help their parents. Most of Ae Ba'i's children only graduated from elementary school, and it is difficult to continue to a higher level because of high school fees and the community's very narrow understanding of education.